2017
DOI: 10.1371/journal.pone.0172970
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of marine traffic on the behaviour of Black Sea harbour porpoises (Phocoena phocoena relicta) within the Istanbul Strait, Turkey

Abstract: Marine traffic is threatening cetaceans on a local and global scale. The Istanbul Strait is one of the busiest waterways, with up to 2,500 vessels present daily. This is the first study to assess the magnitude of short- and long-term behavioural changes of the endangered Black Sea harbour porpoises (Phocoena phocoena relicta) in the presence of marine vessels within the Istanbul Strait. Markov chains were used to investigate the effect of vessel presence on the transition probability between behavioural states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
(76 reference statements)
2
4
0
Order By: Relevance
“…Our findings add valuable insights into how cetaceans respond to vessel disturbance. While porpoises in our study reacted similarly to those observed by Baş et al (2017) and Oakley et al (2017), other studies have documented porpoises to react to vessels over 1 km away (Palka & Hammond, 2001;Wisniewska et al, 2018). This variance underscores the necessity of employing diverse methods to assess the impact of vessels contextually, even within the same species.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Our findings add valuable insights into how cetaceans respond to vessel disturbance. While porpoises in our study reacted similarly to those observed by Baş et al (2017) and Oakley et al (2017), other studies have documented porpoises to react to vessels over 1 km away (Palka & Hammond, 2001;Wisniewska et al, 2018). This variance underscores the necessity of employing diverse methods to assess the impact of vessels contextually, even within the same species.…”
Section: Discussionsupporting
confidence: 53%
“…However, this was not what we observed. In a study of Black Sea harbour porpoises in Istanbul Strait, Turkey, porpoises tended to turn more when vessels were nearby (<200 m; Baş et al., 2017 ). A likely reason for this difference could be the fine resolution of our data, which was collected at 1‐second intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As odontocetes, harbor porpoises rely on sound for orientation, predation and intraspecific communication (Clausen et al, 2010;Wisniewska et al, 2016;Sørensen et al, 2018), which is why they are particularly vulnerable to underwater noise and any hearing impairment should be prevented. Beside impulsive noise events, the global underwater soundscape is largely dominated by shipping noise proven to have negative effects on harbor porpoise behavior (Hermannsen et al, 2014;Dyndo et al, 2015;Akkaya Bas et al, 2017;Wisniewska et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, of the porpoise species, only harbor porpoises (Phocoena phocoena) and finless porpoises (Indo-Pacific, Neophocaena phocaenoides; Yangtze, N. asiaeorientalis asiaeorientalis) have been studied with regards to the impact of watercraft. Harbor porpoises moved away from vessels (Palka and Hammond, 2001), showed higher levels of porpoising in the presence of boats (Dyndo et al, 2015), changed behavioral states (Akkaya Bas et al, 2017), reduced foraging behavior (Wisniewska et al, 2018), and experienced decreased communication ranges (Hermannsen et al, 2014). Acoustic tags (DTAGs) placed on harbor porpoises in Danish waters showed that animals encountered vessel noise 17-89% of the time, and exhibited vigorous fluking, bottom diving, interrupted foraging, and cessation of echolocation during some high vessel noise events (received level > 96 dB re 1 µPa at 16 kHz 1/3 octave band; Wisniewska et al, 2018).…”
Section: Odontocetesmentioning
confidence: 99%